Interest and aesthetic towards quatrains - Abd Rahim, Normaliza; Roslan, Nur Maisarah; Roslan, Nur Widad (Human Resource Management Academic Research Society, 2020)
Malay quatrain was introduced to students who studied Malay language and literature in the universities from all over the world. It is one of the Malay literature genres. Therefore, this study aims to introduce Malay quatrain among Korean learners. The objectives of the study are to investigate and discuss Korean students’ perceptions and aesthetic values toward Malay quatrains. The subjects of the study involved a class of 18 university students in one of the universities in South Korea. All of the subjects are majoring in Malay-Indonesian Interpretation and Translation, thus, they have been exposed to Malay quatrains in the previous semester. The subjects were interviewed informally on their perceptions toward Malay quatrains. The subjects were divided into groups of threes and fours in order for them to discuss the Malay quatrain. The results of the study found that the subjects showed great interest and understanding toward the Malay quatrain and moreover, they had learned the aesthetic values in the Malay quatrains. The study has given implication toward educators and students who studied Malay language and literature in appreciating the Malay quatrain. It is hoped that future research will investigate in depth on the aesthetic values of two stanzas of Malay quatrains.